Aged care facilities and primary health‐care clinics provide appropriate settings for dietetic students to demonstrate individual case management clinical competence. Issue 1 (17th November 2014) - Bacon, Rachel; Williams, Lauren; Grealish, Laurie
Abstract Aim The aims of this study were to: (i) determine the ways in which non‐hospital placement settings are used for individual case management clinical placements in dietetic education and (ii) examine the extent to which students can develop individual case management clinical competencies in non‐hospital placement settings. Methods A sequential mixed methods approach was used. Quantitative data were obtained from an online questionnaire conducted with placement coordinators from all 15 Australian universities with accredited dietetics programs. Qualitative data were obtained from a focus group with eight experienced clinical supervisors who had viewed 11 audiovisual recordings of student/dietitian encounters with clients in non‐hospital settings and assessed them against entry‐level competencies. Data were analysed using descriptive statistics and content analysis. Results Placement coordinators from 10 of the 15 accredited universities responded, with most universities (8/10) using hospitals for the majority of their individual case management clinical placements. Seven of the ten universities used non‐hospital settings but only for a small proportion of students (≤25%) and for short durations (one to two weeks). The experienced clinical supervisors agreed that primary health‐care clinics and residential aged care facilities provided appropriate practice settings for student dietitians to demonstrate individual case management clinical competencies. Conclusions To align with the national health‐care agenda and workforce demands, this research supports the expansion of clinical placement settings to also include non‐hospital settings. The influence of context on competency development requires adjustments to be made for the nuanced practice differences in these settings.